Plant Extract-Synthesized Silver Nanoparticles for Application in Dental Therapy - Omnia Ahmed; Nicole Remaliah Samantha Sibuyi; Adewale Oluwaseun Fadaka; Madimabe Abram Madiehe; Ernest Maboza; Mervin Meyer; Greta Geerts (Pharmaceutics, 2022)
Oral diseases are the most common non-communicable diseases in the world, with dental caries and periodontitis causing major health and social problems. These diseases can progress to systematic diseases and cause disfigurement when left untreated. However, treatment of oral diseases is among the most expensive treatments and often focus on restoration of form and function. Caries prevention has traditionally relied on oral hygiene and diet control, among other preventive measures. In this paper, these measures are not disqualified but are brought into a new context through the use of nanotechnology-based materials to improve these conventional therapeutic and preventive measures. Among inorganic nanomaterials, silver nanoparticles (AgNPs) have shown promising outcomes in dental therapy, due to their unique physicochemical properties and enhanced anti-bacterial activities. As such, AgNPs may provide newer strategies for treatment and prevention of dental infections. However, numerous concerns around the chemical synthesis of nanomaterials, which are not limited to cost and use of toxic reducing agents, have been raised. This has inspired the green synthesis route, which uses natural products as reducing agents. The biogenic AgNPs were reported to be biocompatible and environmentally friendly when compared to the chemically-synthesized AgNPs. As such, plant-synthesized AgNPs can be used as antimicrobial, antifouling, and remineralizing agents for management and treatment of dental infections and diseases.